Comparative transcriptomics analyses of chemosensory genes of antenna in male red swamp crayfish Procambarus clarkii - Zhou, Zihao; Mo, Lili; Li, Dinghong; Zeng, Wenlong; Wu, Hongying; Wu, Zhengjun; Huang, Jinlong (Frontiers in Ecology and Evolution, 2022)
The red swamp crayfish, Procambarus clarkii, is a globally invasive species and has caused huge damage to aquaculture, biodiversity, and ecology worldwide. Antenna-expressed receptors are important for P. clarkii to detect chemosensory cues for mate attraction. In this study, we tested the behavior of male P. clarkii to the conditioned water from female P. clarkii during the mating and non-mating periods, and performed RNA sequencing to investigate the chemosensory-related genes of the antenna of male P. clarkii. The results of the behavioral assay have shown that for the female-conditioned water, male P. clarkii within the mating period can be significantly attracted, but not during the non-mating period. This suggested that the expressions of chemosensory-related genes in the antenna of male P. clarkii may change significantly with mating seasonal variation. Antenna transcriptomes found that a total of 59,218 unigenes with an average length of 1,056.41 bp, and 4,889 differentially expressed unigenes (DEGs), among which 2,128 were upregulated, while 2,761 were downregulated were obtained. A total of 12 upregulated and nine downregulated DEGs were associated with chemical reception, including four ionotropic receptors (IRs) or ionotropic glutamate receptors (iGluRs), eight G-protein-coupled receptors (GPCRs), five transient receptor potential channels (TRP channels), one sodium–calcium exchanger, one isomerase, and two uncharacterized proteins (chemosensory proteins-like, CSPs). CSPs were preliminarily classified as pheromone receptors in the antenna of male P. clarkii. Furthermore, the calcium transduction-related pathways may play an important role in the sex pheromone reception of the male P. clarkii’s antenna. The results of quantitative real-time reverse transcriptase PCR (RT-qPCR) showed that the trends of expression of eight selected unigenes were consistent with RNA-Seq results. Our results provide more comprehensive data for chemical communication mechanisms after P. clarkii enter the mating period and eventually would develop better control strategies in further.